2008
DOI: 10.1158/1078-0432.ccr-07-4491
|View full text |Cite
|
Sign up to set email alerts
|

Pathologic Complete Response to Neoadjuvant Chemotherapy of Breast Carcinoma Is Associated with the Disappearance of Tumor-Infiltrating Foxp3+ Regulatory T Cells

Abstract: Purpose: T-cell infiltration is associated with good tumor prognosis in many cancers. To assess the capacity of neoadjuvant chemotherapy to affect T-cell infiltration in breast cancer, we evaluated CD3 and CD8 infiltrates, and the Foxp3 immunosuppressive Tcells. Experimental Design: CD3 + , CD8 + , and Foxp3 + cell infiltrates were detected by immunohistochemistry in a series of 56 breast cancer patients before and after the end of neoadjuvant chemotherapy. Results: Poor prognostic factors (negative hormonal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
247
2
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(260 citation statements)
references
References 24 publications
9
247
2
2
Order By: Relevance
“…Recent studies have also shown that successful chemotherapeutic treatments for breast carcinoma, which resulted in a complete pathologic response also resulted in the disappearance of FoxP3-positive T cells and an increased number of CD8 þ cytotoxic T cells. 31 We observed associations between elevated numbers of FoxP3-positive cells and the more aggressive tumor phenotypes of advanced Nottingham grade (grade III) and larger tumor size (42.0 cm). One of the most aggressive breast cancer phenotypes, the so-called 'triple negative' (ER, PR, and Her2/neu) Nottingham grade III cancer, was also significantly associated with higher average numbers of FoxP3-positive cells.…”
Section: Discussionmentioning
confidence: 64%
“…Recent studies have also shown that successful chemotherapeutic treatments for breast carcinoma, which resulted in a complete pathologic response also resulted in the disappearance of FoxP3-positive T cells and an increased number of CD8 þ cytotoxic T cells. 31 We observed associations between elevated numbers of FoxP3-positive cells and the more aggressive tumor phenotypes of advanced Nottingham grade (grade III) and larger tumor size (42.0 cm). One of the most aggressive breast cancer phenotypes, the so-called 'triple negative' (ER, PR, and Her2/neu) Nottingham grade III cancer, was also significantly associated with higher average numbers of FoxP3-positive cells.…”
Section: Discussionmentioning
confidence: 64%
“…In line with these results, it has been shown that clinical response to chemotherapy is often associated with a reduction in TITregs and the recruitment of intratumoral CD8 + T cells [95]. Moreover, imatinib mesylate (a small agent initially developed as a BCR-ABL-specific inhibitor) has been demonstrated to potentiate antitumor T-cell responses in patients affected by gastrointestinal stromal tumors by inhibiting IDO expression (by tumor cells) and hence promoting the apoptotic demise of Tregs [96].…”
Section: Clinical Significance Of Intratumoral Tregsmentioning
confidence: 83%
“…In breast cancer patients receiving neoadjuvant chemotherapy, a higher intratumoral CD8 þ /FoxP3 ratio has been correlated with a favorable response to the treatment, as compared with unchanged ratios in nonresponders. 17 Particularly, this treatment resulted in a decrease in FoxP3 þ , but no change in CD8 þ and CD3 þ T-cell infiltrates, with a significant increase in cytotoxic markers, such as TiA1 and granzyme B. 17 It is noteworthy that the LmddA vector expressing an irrelevant antigen (HPV16 E7) was also associated with a significant decrease in the frequency of Tregs in the tumors, likely as a consequence of innate immunity responses.…”
Section: Discussionmentioning
confidence: 99%
“…17 Particularly, this treatment resulted in a decrease in FoxP3 þ , but no change in CD8 þ and CD3 þ T-cell infiltrates, with a significant increase in cytotoxic markers, such as TiA1 and granzyme B. 17 It is noteworthy that the LmddA vector expressing an irrelevant antigen (HPV16 E7) was also associated with a significant decrease in the frequency of Tregs in the tumors, likely as a consequence of innate immunity responses. The ability of bacteria to silence Tregs has been already described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation